2013
DOI: 10.4103/1755-6783.127805
|View full text |Cite
|
Sign up to set email alerts
|

A case of clinically inapparent bilateral adrenal histoplasmosis in an Immunocompetent person

Abstract: Histoplasmosis presenting as bilateral large adrenal masses is rare. We describe the case of a 35-year-old male with bilateral adrenal masses which turned out to be histoplasmosis on biopsy, so the masses were treated with antifungal agents. We describe the case for its rarity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 4 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…Shirangarpure et al, Goswami et al, and Goodwin et al reported adrenal involvement in chronic disseminated form . Carvalho et al and Kaufmann also reported adrenal histoplasmosis .…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Shirangarpure et al, Goswami et al, and Goodwin et al reported adrenal involvement in chronic disseminated form . Carvalho et al and Kaufmann also reported adrenal histoplasmosis .…”
Section: Discussionmentioning
confidence: 95%
“…While smearing, the fragile cytoplasm of the macrophages may get disrupted; hence this organism can also be seen extracellularly . It is surrounded by a clear ring of space that resembles a capsule, hence the misnomer, H. capsulatum . Many scattered stripped epithelial cells of adrenal gland origin, scattered lipid globules and inflammatory cells may be seen against a dense necrotic amorphous background .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations